How does “Fun at Work” work for Learning Advisors in Aotearoa-New Zealand? - Owler, K; Morrison, RL (Association of Tertiary Learning Advisors of Aotearoa New Zealand (ATLAANZ), 2015)
Job satisfaction and motivation are vital to ensuring productivity and business success. As part of enhancing student success in a fast changing world, it is necessary for Tertiary Learning Advisors (TLAs) to be motivated and have fun at work. This paper draws on Herzberg’s (1966) two-factor theory of worker motivation to explore factors contributing to dissatisfaction and motivation for TLAs in Aotearoa/New Zealand. In Herzberg’s model, the absence of “hygiene” factors leads to dissatisfaction for workers, whereas the presence of “satisfiers” result in satisfaction or motivation. We conducted a textual analysis of three volumes of ATLAANZ conference proceedings in order to identify the main hygiene and motivation factors experienced by TLAs in Aotearoa/New Zealand. Hygiene factors included security and status stemming from the “neo-liberal” reforms taking place in learning institutions. Satisfiers included growth, relationship with peers and the work itself. Findings should assist management in seeking to maximise opportunities for TLA satisfaction, while aiming to moderate the strain of institutional change. Individual TLAs may also find it useful to know what others find motivating and fun, incorporating these strategies into their own work-life.
Keywords: Herzberg; Tertiary learning advisor; Worker motivation; Fun at work; Worker satisfaction; Worker dissatisfaction